The Application of Marketing Mix Strategy in Increasing the Percentage of Customer Interest in Funding Products at BSI KCP Situbondo A Yani - Muh Hamzah; Mohammad Syaiful Suib; Farisa Irwayu (IJED: International Journal of Economy Development Research, 2022)
Marketing strategy is one way to win a sustainable competitive advantage for a company. The marketing strategy can be viewed as one of the bases used in preparing the overall company plan. This study aimed to determine the application of the marketing mix strategy in increasing the percentage of customer interest in funding products at BSI KCP Situbondo A. Yani. This study uses a qualitative method with a descriptive approach. Data collection is done through observation, interviews, documentation, or reports describing the research’s object. The results and research are elements of the marketing mix consisting of product, price, place process, promotion, people, and physical evidence carried out by BSI KCP Situbondo A. Yani are pretty good. Based on the first study’s results, BSI KCP Situbondo A Yani has implemented the 7P marketing mix strategy well. Second, the amount of funding at BSI KCP Situbondo A Yani will increase in 2022 after experiencing a significant decline from 2020 to 2021 during the Covid-19 pandemic. And thirdly, there is an increase in the number of customers interested in using funding, lending products and increasing income every month. The application of the marketing mix in increasing the percentage of customer interest in funding products carried out by BSI KCP Situbondo A. Yani is reasonably practical because there is an improvement in the number of customers from time to time